Brain Networks Underlying Strategy Execution and Feedback Processing in an Efficient Functional Magnetic Resonance Imaging Neurofeedback Training Performed in a Parallel or a Serial Paradigm - Dewiputri, Wan Ilma; Schweizer, Renate; Auer, Tibor (Frontiers in Human Neuroscience, 2021)
Neurofeedback is a complex learning scenario as the task consists of trying out mental strategies while processing a feedback signal that signifies activation in the brain area to be self-regulated and acts as a potential reward signal. In an attempt to dissect these subcomponents, we obtained whole-brain networks associated with efficient self-regulation in two paradigms: Parallel, where the task was performed concurrently, combining feedback with strategy execution; and Serial, where the task was performed consecutively, separating feedback processing from strategy execution. Twenty participants attempted to control their anterior midcingulate cortex (aMCC) using fMRI neurofeedback in 18 sessions over 2 weeks using cognitive and emotional mental strategies. We analyzed whole-brain fMRI activations in the neurofeedback training runs with the largest aMCC activation for the Serial and Parallel paradigms. The equal length of the strategy execution and the feedback processing periods in the Serial paradigm allows a description of the two task subcomponents with equal power. The resulting activation maps were spatially correlated with functionally annotated intrinsic connectivity brain maps. Brain activation in the Parallel condition correlates with the basal ganglia network, the cingulo-opercular network (CON), and the frontoparietal control network (FPCN); brain activation in the Serial strategy execution condition with the default mode network (DMN), the FPCN, and the visual processing network; while brain activation in the Serial feedback processing condition predominantly with the CON, the DMN, and the FPCN. Additional comparisons indicate that basal ganglia activation is characteristic to the Parallel paradigm, while supramarginal gyrus and superior temporal gyrus activations are characteristic to the Serial paradigm. The multifaceted view of the subcomponents allows describing the cognitive processes associated with strategy execution and feedback processing independently in the Serial feedback task and as combined processes in the multitasking scenario of the conventional parallel feedback task.